2007
DOI: 10.1080/00207450701239442
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia Gravis Accompanied by Thymomas Not Related to Foamy Virus Genome in Belarusian’s Patients

Abstract: The spectrum and features of neurological disorders have been changed due to the Chernobyl catastrophe in the Republic of Belarus. More recently neurologists in Belarus have noted a significant increase in the frequency of myasthenia gravis (MG) with concomitant rise in the thymomas. There is some evidence suggesting that retroviruses play a key role in the development and pathogenesis of autoimmune diseases. This study analyzed thymomas from 45 MG patients from the Republic of Belarus by using PCR and primers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Two reports described detection of human foamy virus, a retrovirus, in patients with thymoma or myasthenia gravis (26,27), but subsequent larger studies did not confirm the findings (28,29). In 2002, Manca et al reported finding evidence for human T-cell lymphotropic virus type 1 infection in myasthenia gravis patients, some of whom had thymoma (30), but again these findings were not confirmed (28).…”
Section: Possible Risk Factors For Thymomamentioning
confidence: 99%
“…Two reports described detection of human foamy virus, a retrovirus, in patients with thymoma or myasthenia gravis (26,27), but subsequent larger studies did not confirm the findings (28,29). In 2002, Manca et al reported finding evidence for human T-cell lymphotropic virus type 1 infection in myasthenia gravis patients, some of whom had thymoma (30), but again these findings were not confirmed (28).…”
Section: Possible Risk Factors For Thymomamentioning
confidence: 99%
“…Samples were screened for multiple pathogens as described in detail elsewhere, including: leptospira and anthrax [17], herpesviruses [18], filoviruses [19], paramyxoviruses [20], coronaviruses [21], flaviviruses [22], orthopoxviruses [23] and simian retroviruses (SIV, STLV, SFV) [24][25][26][27][28][29]. All PCR-amplified bands approximately the expected size were confirmed by sequencing.…”
Section: Microbial Screeningmentioning
confidence: 99%